Jacqueries: Mind Games, Street Action, and the Art of the Heist. - Niedzwiecki, Jacob (Canadian Theatre Review)
Choreographer, film-maker, and software developer Jacob Niedzwiecki describes the process of creating Jacqueries, a site-specific, promenade-style, dance/theatre work. Niedzwiecki reveals the discoveries made and the challenges faced by the project's creative team as they applied the concept of information asymmetry in a theatrical context. The work's vocabulary integrates movement from contemporary dance and parkour, as well as gestures from American Sign Language. Its dramaturgy has small groups of audience using a custom-built iPhone app to follow characters through dense urban spaces in a heist narrative with a political edge. Niedzwiecki's Cohort code framework synchronizes playback of music (via headphones), video, and augmented reality on mobile devices for audience, cast, and crew. Jacqueries is an example of using off-the-shelf mobile technology to build an immersive, intimate theatrical experience in outdoor, urban locales.